Baculovirus-vectored multistage Plasmodium vivax vaccine induces both protective and transmission-blocking immunities against transgenic rodent malaria parasites. - Mizutani, M; Iyori, M; Blagborough, A; Fukumoto, S; Funatsu, T; Sinden, R; Yoshida, S (American Society for Microbiology, 2014)
A multistage malaria vaccine targeting the pre-erythrocytic and sexual stages of Plasmodium could effectively protect individuals against infection from mosquito bites and provide transmission-blocking (TB) activity against the sexual stages of the parasite, respectively. This strategy could help prevent malaria infections in individuals and, on a larger scale, prevent malaria transmission in communities of endemicity. Here, we describe the development of a multistage Plasmodium vivax vaccine which simultaneously expresses P. vivax circumsporozoite protein (PvCSP) and P25 (Pvs25) protein of this species as a fusion protein, thereby acting as a pre-erythrocytic vaccine and a TB vaccine, respectively. A new-concept vaccine platform based on the baculovirus dual-expression system (BDES) was evaluated. The BDES-Pvs25-PvCSP vaccine displayed correct folding of the Pvs25-PvCSP fusion protein on the viral envelope and was highly expressed upon transduction of mammalian cells in vitro. This vaccine induced high levels of antibodies to Pvs25 and PvCSP and elicited protective (43%) and TB (82%) efficacies against transgenic P. berghei parasites expressing the corresponding P. vivax antigens in mice. Our data indicate that our BDES, which functions as both a subunit and DNA vaccine, can offer a promising multistage vaccine capable of delivering a potent antimalarial pre-erythrocytic and TB response via a single immunization regimen.